Myelodysplastic syndrome (MDS)/Myeloproliferative neoplasm (MPN) with loss of long arm of chromosome 5 (del 5q): Clinical case and treatment perspectives. - Khurdepa , Kateryna; Karnabeda , Oksana (The Ukrainian Scientific Medical Youth Journal, 2024)
this clinical case report presents a patient diagnosed with a myelodysplastic syndrome (MDS)/myeloproliferative neoplasm (MPN), specifically myelofibrosis with a deletion of the long arm of chromosome 5 (del 5q), an exceedingly rare anomaly in chronic myeloproliferative disorders. We performed a thorough analysis of the patient’s clinical, laboratory, and molecular-genetic characteristics to evaluate their impact on prognosis, treatment decisions, and therapeutic outcomes. After excluding other genetic abnormalities, the patient was treated with lenalidomide and prednisolone, resulting in improved clinical and hematological parameters. These findings are consistent with previous studies and suggest the potential efficacy of lenalidomide in treating patients with MDS/MPN characterized by del 5q, especially when no additional genetic abnormalities are present.